Screening for psychologic distress in Taiwanese cancer inpatients using the National Comprehensive Cancer Network distress thermometer: the effects of patients’ sex and chemotherapy experience - Chiou, Y-J; Lee, C-Y; Li, S-H; Chong, M-Y; Lee, Y; Wang, L-J (Elsevier, 2017)
Background Patients with cancer often experience distress, and early detection and management of psychologic distress are vital for improving patients’ outcomes.